Enhancing the productivity of farmer community in producing organic fertilizer and local plant-based pesticide - I Ketut Widnyana; Ni Putu Pandawani; Putu Edi Yastika; I GD Yudha Partama; I Made Wahyu Wijaya (Journal of Community Service and Empowerment, 2023)
These activities are expected to improve the agriculture community resilience in Batukaang Village to achieve a sustainable agriculture practice. Through a training and assisting program, the farmer community will get improved their skill to make their own fertilizer and pesticide by utilizing organic waste and local material. These activities contribute to the achievement of SDG 2: Zero hunger, since agriculture in Batukaang Village is the most sector that support the economics and food security. The activities resulted in increasing the knowledge and skill of farmer community in Batukaang Village. By enhancing the farmers with the knowledge, skills, and resources required to produce their own organic fertilizer and pesticide, they can promote soil health, reduce environmental pollution, and enhance the well-being of agricultural communities as a whole. It support resilient agricultural systems that promote sustainable practices, safeguard natural resources, and enhance farmers' livelihoods in Batukaang Village.